An Approach to Whole-Genome Identification of IRES Elements - Graber, Tyson E.; Lewis, Stephen M.; Holcik, Martin (Current Genomics, 2006)
Spatial and temporal control of proteome expression is critical for cellular homeostasis. The ability to regulate polypeptide synthesis allows the cell to rapidly respond to changes in its environment. Under stress conditions, capdependent translation initiation is downregulated and alternative mechanisms of translation initiation are favoured for the production of critical proteins that ultimately determine whether the cell is able to overcome the stress. One such alternative mechanism of translation initiation is mediated by sequence elements located downstream of the 5' cap structure that are able to directly recruit ribosomes to a region proximal to the translation start site. Identifying the eukaryotic mRNAs that contain such internal ribosome entry sites (IRESes) is an important first step in cataloguing the cellular complement of proteins whose expression is translationally regulated during cellular stress and understanding how cells regulate translation under stress conditions. To date, no consensus sequence motif or structure has been identified as a signature of cellular IRES activity, making it difficult to identify the full complement of eukaryotic IRESes. This review will underscore the challenges faced in identifying IRESes on a genomic scale and potential solutions will be presented.
Keywords: stress